A pilot study on high intensity functional training in an adaptive population - Andrews, Victor (Kansas State University, 2019)
Introduction: There are currently more than 56 million adults in the U.S. living with a disability that may affect activities of daily living and quality of life (QoL). Disabilities and chronic conditions may place impairments that limit participation in physical activity due to needing adaptations in order to be physically active. Physical activity is helpful in the prevention of secondary health conditions for those with an adaptive need. This pilot study investigated the effectiveness of adaptive high intensity function training (HIFT) for improving self-reported activity limitations and participation restrictions, QoL, sport/exercise beliefs, physical activity self-efficacy and enjoyment, and measured basic human movements (BHM). Methods: A two site pilot study was conducted using a single condition pre-test posttest design to provide an 8-week adaptive HIFT intervention to those with an adaptive need (e.g., cane, wheelchair). Eight participants (62.5% male, 37.5% White, 37.5% Black, 25% Hispanic/Latino, 100% with some college education or more) completed 2-3, 60-minute exercise sessions per week of high intensity, low volume workouts with trainers certified in adaptive HIFT. Participants completed online surveys including the World Health Organization QoL-BREF, the outpatient physical therapy improvement in movement assessment log (OPTIMAL), sport and exercise ability, and physical activity self-efficacy and enjoyment. BHM including the squat, lunge, rotation, push-up, brace, and hinge were directly measured via photographs. Results: While all 8 participants completed the exercise intervention, only 2 participants completed pre-test and post-test surveys, and 7 completed the BHM assessments at pre- and posttest. Participants reported baseline physical activity limitations involving walking and moving, coordination, balance, and agility. All other measures were within normal ranges or relatively high at baseline. Squatting was the lowest rated BHM at baseline. Descriptive analysis for the two participants showed small-to-large percent changes in self-reported measures, with the largest improvements in Subject 1’s sport/exercise ability ratings. Despite a lack of statistical significant differences, changes in BHM scores had medium effect sizes for the squat (d = 0.637), brace (d = 0.624) and lunge (d = 0.501). Conclusion: Adaptive HIFT may be beneficial to those with adaptive needs due to the ability to scale and modify movements to allow for inclusion of those with a disability or chronic conditions that require activity adaptations. Future research should study the effects of an adaptive HIFT program in a fully-powered randomized controlled trial with a larger group of adaptive athletes.
Keywords: Physical activity; Disability; High intensity functional training